Trade Dependency Within a Volatile Union: The Gulf Cooperation Council Case - Glnar Eskandar (ZBW - Leibniz Information Centre for Economics, 2022)
The Gulf Cooperation Council (GCC) has faced serious challenges to its credibility as an economic union. Comprising six nation-states (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) on the premise of sharing common national objectives, the GCC's recent past is marred by intra-bloc political disagreements that even led to a trade embargo against one of its member states. These internal tensions were coupled with sobering negative externalities, such as fluctuations in energy prices and the COVID-19 pandemic, further impacting the union's economies. Despite these hurdles, this study shows, GCC intra-bloc trade dependence increased over the past decade, especially following episodes of negative external shocks affecting overall trade. Bahrain, Oman, and the UAE have grown the most dependent on the bloc for trade, with the former two particularly reliant on GCC imports to meet their domestic demands, and the latter reliant on the bloc as a significant export destination. By comparison, Saudi Arabia, Qatar, and Kuwait are the least dependent on the bloc. Viewing high trade dependency on growingly volatile neighbors as a vulnerability, this paper highlights the GCC member states most exposed to intra-bloc trade shocks. A closer look reveals heavy commodity-specific intra-bloc dependence, one that could lead to major disruptions in Bahrain and Oman's economies should another intra-bloc trade embargo ensue. The study also uncovers a major hiccup to future GCC trade integration: Saudi Arabia, the GCC's biggest market and the second largest contributor to intra-bloc trade, has the least to gain from trading with its neighbors.
Conference: 2022 Gulf Research Meeting, held at the University of Cambridge, organized by the Gulf Research Centre Cambridge (GRCC)
Keywords: F14; F15; F63; O53; F51; 330; Gulf Cooperation Council (GCC); trade dependence; export propensity; import penetration; intra-bloc